The Adjustment of VaR to the Empirical Distribution of Returns - Radu Lupu (Theoretical and Applied Economics, 2006)

(untitled)
Basel II Recommendations concerning internal rating based models approach for financial institutions and the success of RiskMetrics made Value-at-Risk (VaR) is the most important risk measurement instrument at international level. The objective of this paper is to address the problem of adapting this method to the statistical properties of the returns for portfolios that include derivatives in the form of options too. We assume that the returns for the analyzed portfolios are not normally distributed. The methodologies presented are the ones used to capture the percentile when returns follow the features of the empirical distributions reviewed in Cont (2001).